Analisis Dampak Covid-19 Terhadap Efisiensi, Efektivitas, dan Produktivitas Rumah Sakit (Studi kasus: RSU Mitra Paramedika D.I. Yogyakarta) - Ichsan Priyotomo; Muhammad Syamsu Hidayat; Lina Handayani (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Changes in government policy in response to the increase in COVID-19 cases have caused delays in services and restrictions on services in hospitals. Increasing the fulfillment of hospital operational needs related to COVID-19 cases has an impact on increasing hospital operating costs. The purpose of this study was to determine the impact of COVID-19 on the efficiency, effectiveness and productivity of hospital services. The type of research used is a mixed method with a triangulation design approach. Qualitative data obtained by conducting in-depth interviews. The research subjects are the leadership ranks of Mitra Paramedika Hospital, while the object of the research is documents related to the efficiency, effectiveness and productivity of the hospital. Quantitative data was obtained by using documents such as visit reports, financial reports and other documents related to this research. Effectiveness data was analyzed by calculating the effectiveness ratio, efficiency data was analyzed by calculating the efficiency ratio, and productivity data was analyzed using Data Envelopment Analysis (DEA) with the help of the DEAP application. The results showed that there was no impact of COVID-19 on hospital efficiency and productivity, but there was an impact of COVID-19 on hospital effectiveness.